PEMANFAATAN PLATFORM CANVA UNTUK PENINGKATAN LITERASI DESAIN GRAFIS SISWA DALAM KEGIATAN KAMPANYE SEKOLAH - Jailani, Ahmad; Kholilah, Dilafatul; Riandita, Nabila (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2025)
Graphic design skills are becoming essential competencies to support visual communication in the digital era, especially within educational environments. However, many educational institutions have not yet optimized the use of visual media to effectively convey educational messages, including in school campaign activities. This article discusses the results of a community service activity in the form of a graphic design training using the Canva platform for students at MA Miftahul Ulum Besuki. The activity aimed to improve students' graphic design literacy and produce visual works such as posters and brochures that are engaging, communicative, and relevant to school-related issues. The implementation method involved hands-on practice, project-based learning, and intensive mentoring in using Canva. The results show a significant improvement in students' technical and conceptual skills in designing educational visual content. The produced materials were also utilized directly by the school for PPDB (new student enrollment) campaigns and other social promotions. This article's discussion highlights Canva as an effective, inclusive, and adaptable platform for enhancing students’ graphic design capabilities in the digital age. This activity is recommended to be replicated in other schools as a strategy for strengthening students' digital literacy and creativity.